1989
DOI: 10.2307/1242035
|View full text |Cite
|
Sign up to set email alerts
|

Profit Function Approximations and Duality Applications to Agriculture

Abstract: Monte Carlo simulations of profit functions indicate that flexible functional forms may be ranked nearly the same with respect to Allen-Uzawa partial substitution elasticities or price and fixed factor elasticities. Flexible functional form approximations of output price elasticities are generally worse than approximations of input price or fixed factor elasticities. Minflex Laurent functional forms did not appear to approximate underlying elasticities any better than did their translog and generalized Leontie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The effect of choice of functional form on the ability to recover dual results has also been studied (e.g. Thompson and Langworthy 1989). The normalised quadratic form was chosen as both: (i) the true underlying technological data-generating process; and (ii) the flexible functional form used for estimating the profit, restricted profit and production functions.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of choice of functional form on the ability to recover dual results has also been studied (e.g. Thompson and Langworthy 1989). The normalised quadratic form was chosen as both: (i) the true underlying technological data-generating process; and (ii) the flexible functional form used for estimating the profit, restricted profit and production functions.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…However, Chambers and Quiggin (1998) illustrated that, in some cases, cost functions can be theoretically derived from stochastic production functions, and Coyle (1999) and Pope and Just (1998) suggested alternative methods of estimating cost and profit functions under risk aversion. Thompson and Langworthy (1989) illustrated that elasticities calculated from primal and dual approaches depend on the choice of functional form. They showed that identical results will never be obtained from primal and dual approaches unless the flexible functional form is selfdual (such as the quadratic) and the underlying data-generating process identically matches the chosen functional form.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons for adopting the normalized quadratic functional form (4) in the present study. First, this function has been broadly employed in applications of the duality approach (Huffman and Evenson 1989; Thompson and Langworthy 1989;Shumway and Lim 1993;Lusk et al 2002;Arnade and Kelch 2007;Schuring, Huffman, and Fan 2011). Second and most important, the normalized quadratic function is self-dual, with the Hessian matrix of the profit and production functions depending on parameters only.…”
Section: The Model Of Individual Firmsmentioning
confidence: 99%
“…Considerable effort has been put into testing the most appropriate flexible functional form (FFF) for a given dataset (Guilkey, Lovell, and Sickles 1983;Dixon, Garcia, and Anderson 1987;Thompson and Langworthy 1989), because the utilized FFF drives the results. Analyses of this type usually consist of the following steps.…”
mentioning
confidence: 99%
“…Pope (1980) and Pope (1982a) suggested that duality results do not hold for stochastic models. Thompson and langworthy (1989) and Pope and Just (2002) suggest that the functional form may affect elasticity estimates in the primal and dual methods. Lusk et al (2002) underscored the need of high-quality databases to estimate dual relationships in the presence of measurement error and low variability of relative prices for different sample sizes.…”
Section: Introductionmentioning
confidence: 99%